Assessment of Spiritual Intelligence and its Association with Teaching Ability in the Faculty Members of the School of Dentistry - Donia Sadri; Reza Hasanzadeh (Mashhad University of Medical Sciences, 2018)
Introduction: Given the importance of enhancing the teaching ability of faculty members and the influential factors and considering the limited resources in this regard, the present study was conducted to evaluate the spiritual intelligence and its association with teaching ability in the faculty members of the dentistry school at Islamic Azad University in 2015. Materials and Methods: In this analytical-correlational study, the spiritual intelligence of the faculty members was assessed using the Persian version of the standard King's health questionnaire (KHQ), the validity and reliability of which were confirmed. Moreover, the teaching ability of the participants was evaluated using the Persian version of the Alabama standard questionnaire with proper validity and reliability. In the KHQ, spiritual intelligence was scored based on a five-point Likert scale, and teaching ability in the Alabama inventory scale was scored based on a four-point Likert scale. Influential factors, such as age and gender, were also reviewed. Data analysis was performed using the Chi-square and Spearman tests.  Results: In total, 132 questionnaires were distributed among the faculty members of the Dentistry Unit at Islamic Azad University, 96 of which were collected. Mean scores of spiritual intelligence and teaching ability were 58.8±15.4 and 92.1±17.3, respectively. The correlation between the spiritual intelligence and teaching ability of the faculty members was estimated at 0.301. Spiritual intelligence was observed to be higher in the female participants (P